ABSURDITAS DAN INDIVIDUALITAS DALAM ROMAN L’ÉTRANGER KARYA ALBERT CAMUS (KAJIAN SEMIOLOGI ROLAND BARTHES) - Sunahrowi Sunahrowi (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
L’Étranger’s influence on literature, especially on Existentialism, has attracted literary writers and critics. In order to find a text’s meaning and to give a more comprehensive attention to meaning dimension and text plurality, Roland Barthes classified signifiers in narrative discourse into a series of concise and coherent fragments called lexias. And finally, individuality and absurdity constitute the main spirits in Existentialism. L’Étranger expresses aloud these two things just as how Albert Camus shouts out loud his ideology – Existentialism, in each of his works.